Criticism Strategies Found In The Youtube Video “Trevor Noah Unpacks The Racist Response To The Little Mermaid” By The Daily Show - Rakinza Dewina Sari; Agus Wijayanto (Universitas Cokroaminoto Palopo, 2024)
Criticism is one type of oppositional behavior in language. This research aimed to identify the types of criticism strategies and to examine the external pragmatic modifiers used by Trevor Noah in the video Trevor Noah Unpacks the Racist Response to The Little Mermaid. The researcher used a qualitative descriptive method. The data in this research are speech acts of criticism uttered by the speaker (Trevor Noah) whose data source was taken from YouTube video. This research used documentation to collect the data and was analyzed using a qualitative approach with Nguyen's (2005) theory of criticism strategies. The results of this research showed that there were 18 data which contained criticism speech acts found in Trevor Noah's utterances. The data were classified into two types of criticizing strategies including 9 direct criticizing strategies, such as 1 negative evaluation, 2 disapprovals, 2 expressions of disagreement, 3 identifications of problems, and 1 consequence, and 9 indirect criticizing strategies, such as 1 correction, 2 indicating standards, 1 demand for change, 2 requests for change, while expressions of uncertainty, asking/presupposing, and other hints (sarcasm), each found one utterance. The researcher also found 4 classifications of external pragmatic modifiers used to mitigate criticism, such as steers, sweeteners, disarmers, and grounders contained in Trevor Noah's utterances.